2023
DOI: 10.1021/acs.est.2c07329
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Intermittent Environmental Hypoxia Promotes Vascular Remodeling through Angiogenesis in the Liver of Largemouth Bass (Micropterus salmoides)

Abstract: In this study, we explored the effects of 4 weeks of intermittent hypoxic exposure (IHE) on liver angiogenesis and related regulatory mechanisms in largemouth bass (Micropterus salmoides). The results indicated that the O 2 tension for loss of equilibrium (LOE) decreased from 1.17 to 0.66 mg/L after 4 weeks of IHE. Meanwhile, the red blood cell (RBC) and hemoglobin concentrations significantly increased during IHE. Our investigation also found that the observed increase in angiogenesis was correlated with a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Under normoxia, HIF-1α was hydroxylated by PHD while PHD activity was inhibited, and HIF-1α was stabilized and able to accumulate in hypoxia. 53,54 Hence, the decreased HIF gene expression and higher PHD activity showed that the organism could maintain a more stable state in the face of compound environmental stresses. In our study, the hypoxia phenomenon in the liver was not obvious when the fish were exposed to nZnO during extreme environmental stress (Fig.…”
Section: Nzno Reduced the Rabbitfish Mortality Under Extreme Environm...mentioning
confidence: 99%
“…Under normoxia, HIF-1α was hydroxylated by PHD while PHD activity was inhibited, and HIF-1α was stabilized and able to accumulate in hypoxia. 53,54 Hence, the decreased HIF gene expression and higher PHD activity showed that the organism could maintain a more stable state in the face of compound environmental stresses. In our study, the hypoxia phenomenon in the liver was not obvious when the fish were exposed to nZnO during extreme environmental stress (Fig.…”
Section: Nzno Reduced the Rabbitfish Mortality Under Extreme Environm...mentioning
confidence: 99%